Obesity related skin disorders - I. A. Gorlanov; D. V. Zaslavskiy; L. M. Leina; I. R. Milyavskaya (Vestnik Dermatologii i Venerologii, 2017)
Obesity is a serious global problem. In recent years, it has been an increase in patients with obesity. In a review of literature presents data on the effect of obesity on the skin. It is responsible for the development of a number of dermatological diseases, including acantosis nigricans, akrohordony, follicular hyperkeratosis, infectious diseases of the skin. Against the background of obesity worsens psoriasis. The connection between obesity and atopic dermatitis.